Complementary chain competition and fluorescence quenching detection of Deoxynivalenol and analytical applications using a novel aptamer - Mingwei Qin (CyTA - Journal of Food, 2021)
Deoxynivalenol (DON) is a mycotoxin commonly found in cereals and animal feeds, which also is a carcinogen easily soluble in water. So it has drawn considerable interest in food safety. In this study, a specific aptamer named DON-A16 was developed from an immobilized ssDNA library by affinity chromatography column-based the SELEX. The complementary chain competition method for DON detection was established, and its limit of detection (LOD) was 488 ng/mL. Graphene oxide-based fluorescence quenching was developed using DON-A16 with fluorescein (FAM) label; its LOD was 200 ng/mL, and the detection time was 3 h. The recovery rate of fluorescence quenching was also detected in different samples (oat, wheat flour, corn), which showed the commercial DON ELISA kit led to an increase in repeatability, satisfactory recovery and consistency. The three-dimensional structure and the main binding site of of DON-A16 was ultimately obtained by molecular docking simulation.